Lineage networks, land conflicts and rural migration in late socialist China - Liangqun, L; Murphy, R (Routledge, 2006)
A new form of migration in parts of rural China involves the members of small descent groups being pushed out of their residential villages by larger descent groups and relocating to their ancestral villages. Although such households were said to be 'returning' to their ancestral villages it was often decades or centuries since the immigrants' direct family members last had contact with members of their ancestral villages. So the returnees were in fact new immigrants to new communities. This article draws on original fieldwork to consider how the place-claiming activities of revived traditional social networks underpinned this household relocation. Our analysis of this phenomenon contributes to a wider body of literature on the revival of traditional networks in late socialist societies. In particular we suggest that the revival of these networks and their territorialisation of space are responses to the conditions of late socialism such as 'fuzzy' land and property rights, and insecure economic livelihoods.